A Suggested Approach to a Library Building Program - Barker, Bonita (1967)
The preliminary building program suggested in this paper makes use of outlines, graphs, charts, and lists, rather than long-winded paragraphs, to describe the needs, objectives, and philosophy of the library. It is hoped that a short, concise, but detailed, report using these methods will save time and make the report more attractive to read, thereby encouraging the many people who will need to assist in the building planning to use the report.